9=-6w+3(w-6)

Simple and best practice solution for 9=-6w+3(w-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9=-6w+3(w-6) equation:


Simplifying
9 = -6w + 3(w + -6)

Reorder the terms:
9 = -6w + 3(-6 + w)
9 = -6w + (-6 * 3 + w * 3)
9 = -6w + (-18 + 3w)

Reorder the terms:
9 = -18 + -6w + 3w

Combine like terms: -6w + 3w = -3w
9 = -18 + -3w

Solving
9 = -18 + -3w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '3w' to each side of the equation.
9 + 3w = -18 + -3w + 3w

Combine like terms: -3w + 3w = 0
9 + 3w = -18 + 0
9 + 3w = -18

Add '-9' to each side of the equation.
9 + -9 + 3w = -18 + -9

Combine like terms: 9 + -9 = 0
0 + 3w = -18 + -9
3w = -18 + -9

Combine like terms: -18 + -9 = -27
3w = -27

Divide each side by '3'.
w = -9

Simplifying
w = -9

See similar equations:

| 4=12-d | | 15k=k-2 | | -7.6=0.4-4y | | 5x*5=180 | | 2.3x=12 | | 22=4(y+8)-6y | | -7/8x=49 | | -15r=r-7 | | -2+15+x=-4+8 | | 11x+66=21 | | 12=9-c | | 5x+2x+6x= | | 4(n+2)+3(2n+6)= | | 75+64+x=180 | | 7=3m+1 | | 2y+3y=30x | | a(2ab-5c)= | | 2x+y-3x=1 | | 2x-3(-2x+22)=-130 | | 3j+4=10 | | 201=17b+99 | | 6=2-b | | 3(-2-3x)=9x | | 20x+240=240 | | 33x-8-14x=10 | | 8x-8=15x-21 | | 2d+18=2-6(d+7) | | =8.041840047611249e+17 | | 5=1-a | | 0.2s=16 | | =0.2e+17 | | 92=c+3 |

Equations solver categories